Hubungan Islam dan Kristen Abad Modern - Sulkifli; Hasaruddin (PT Rizkarya Cendekia Pustaka, 2025)
The relationship between Islam and Christianity in the modern era has undergone significant transformation compared to medieval periods. This research examines the dynamics of Islamic-Christian relations from the 18th century to the present, analyzing both conflict and cooperation patterns. Using qualitative methodology with historical and sociological approaches, this study explores how modernity, secularization, and globalization have reshaped interfaith dialogue. The findings indicate that while historical tensions persist, new forms of cooperation have emerged through interfaith dialogue initiatives, shared humanitarian concerns, and common responses to secularization challenges. The modern era has witnessed both the intensification of theological debates and the development of more sophisticated frameworks for peaceful coexistence. This research concludes that Islamic-Christian relations in the modern era are characterized by complexity, moving beyond simple conflict narratives toward nuanced understanding of mutual cooperation and respectful coexistence.